(untitled) (Lex Scientia Law Review, 2024)
The purpose of the study was to develop measures aimed at improving administrative procedures when working with personnel policy in the Ministry of Internal Affairs and its structural divisions. The following methods were used: analysis, synthesis, comparison. The research findings indicate that the ongoing reform of personnel policy in Kazakhstan has led to a lack of qualified specialists who can adapt to new conditions. This shortage is due to a shift away from viewing personnel development solely as administrative tasks. Furthermore, there is a need to consider employee motivation more comprehensively. The practical significance of this study lies in the fact that the proposed recommendations can be taken as a basis for the development of personnel policy both in the Ministry of Internal Affairs of the Republic of Kazakhstan in general and in individual structural units belonging to the Department of Internal Affairs of the Republic of Kazakhstan.